Analysis of Conceptual Understanding of Reaction Rate Material Using Four-Tier Multiple Choice Diagnostic Test - Sari, Sandi Danar Cynthia; Nur’aini, Devi Ayu; Apriliyani, Dwi; Fajriyah, Laelatul; Sa'diah, Siti; Sinurat, Lerisma Lehon; Sutisna, Nani Resminingsih; Ardi, Triyanto (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
Due to the abstract nature of the concept of reaction rates, it is one of the chemistry concepts commonly misinterpreted by students. A qualitative descriptive research method was used in this study to measure students’ understanding of the concept of reaction rates and the variables involved. The population of this research consisted of 38 students from the eleventh-grade students at a Senior High School in Serang, Indonesia. A four-tier multiple-choice diagnostic test was used as the research instrument. The results showed that 13.03% understood the concept, 61.84% did not understand the concept, and 25.13% had misconceptions. The results showed that the Four-Level Multiple Choice Test is a valid instrument in uncovering misconceptions in conceptual understanding by distinguishing students who correctly answered through reasoning from students who correctly answered through guessing alone. The catalyst factor showed the highest misconceptions at 73.16%, followed by surface area at 68.95%, temperature at 53.16%, and concentration at 52.11%.